أورام الكارسينوئيد الرئوي - علي, وسيم (Latakia University Journal -Medical Sciences Series, 2016)
تعدّ أورام الكارسينوئيد مجموعة غير شائعة من أورام الرئتين وهي بحاجة لاستئصال جراحي، وتأتي أهمية البحث من قلة الدراسات المجراة عن الكارسينوئيد في بلادنا وبالتالي يمكننا مقارنة نتائج الدراسة مع النتائج العالمية.أُجريت الدراسة بطريقة راجعة من1991 م إلى 2007م على المرضى المشخص لديهم كارسينوئيد رئوي في كل من مشفى الأسد والمواساة الجامعيين، حيث أجريت الجراحة ل61 مريض (65%رجال و35%نساء)، وقد سيطر التوضع المركزي في القصبة الرئيسية أو الفصية لدى 54 مريض، وكانت محيطية لدى 7 مرضى.أُجري استئصال فص رئوي واحد عند 19 مريض، استئصال مع تصنيع قصبي عند 17 مريض (13 مريض مع استئصال جزء من الرئة و4 بدون استئصال أي جزء)، استئصال فصين معاً عند 12 مريض، استئصال رئة عند 12 أيضاً واستئصال قطعي في حالة واحدة.تبيّن بالتشريح المرضي أنّ 51 مريض لديهم كارسينوئيد نموذجي و10 مرضى لا نموذجي، كما تبين بإجراء تجريف كامل للعقد اللمفية أنّ 11 مريض لديهمN1 (إصابة العقد السرية) ومريضين لديهما N2 (إصابة العقد المنصفية).يجب اعتبار الجراحة التي تحافظ على النسيج الرئوي هي العلاج الأساسي وتحمل نتائج جيدة جداً، إلا أنّ الكارسينوئيد اللّانموذجي ذو طبيعة عدوانية حيث يميل إلى إعطاء نقائل للعقد اللمفاوية ويصيب مرضى أصغر سناً.Carcinoids tumors are considered as uncommon lung tumors, which need surgical treatment. Research value comes from the lack in researches about carcinoid in our country, so we can compare our results with global researches. This study is retrospective from 1991 to 2007, 61 patients (65% men and 35% women) were surgically treated for bronchial carcinoids at AL ASSAD and AL MOASSAH Universities Hospitals. The tumors were located centrally, involving main or lobar bronchi in 54 patients and were peripheral in seven.Lobectomy was performed in 19, sleeve resection in 17(a bronchoplastic procedure without resection of lung in four, enucleation in 13), bilobectomy in 12, pneumonectomy in 12 and segmentectomy in one case.Histologically, 51 of the carcinoids wereclassified as typical and 10 as atypical. A formal mediastinal lymph node dissection was done, 11 had N1 disease ( hilar nodes involved ) and two patients had N2 (mediastinal nodes involved). The mainstay of treatment of carcinoids is surgical treatment (which reserve lung parenchyma) in all cases, and has very good results, but atypical carcinoid has aggressive nature and more propensity naved lymph nodes, and occur in younger patients.